High throughput toxicity screening and intracellular detection of nanomaterials. (7th June 2016) - Collins, Andrew R.; Annangi, Balasubramanyam; Rubio, Laura; Marcos, Ricard; Dorn, Marco; Merker, Carolin; Estrela‐Lopis, Irina; Cimpan, Mihaela Roxana; Ibrahim, Mohamed; Cimpan, Emil; Ostermann, Melanie; Sauter, Alexander; et al.
Abstract : Abstract : With the growing numbers of nanomaterials (NMs), there is a great demand for rapid and reliable ways of testing NM safety—preferably using in vitro approaches, to avoid the ethical dilemmas associated with animal research. Data are needed for developing intelligent testing strategies for risk assessment of NMs, based on grouping and read‐across approaches. The adoption of high throughput screening (HTS) and high content analysis (HCA) for NM toxicity testing allows the testing of numerous materials at different concentrations and on different types of cells, reduces the effect of inter‐experimental variation, and makes substantial savings in time and cost. HTS/HCA approaches facilitate the classification of key biological indicators of NM‐cell interactions. Validation of in vitro HTS tests is required, taking account of relevance to in vivo results. HTS/HCA approaches are needed to assess dose‐ and time‐dependent toxicity, allowing prediction of in vivo adverse effects. Several HTS/HCA methods are being validated and applied for NM testing in the FP7 project NANoREG, including Label‐free cellular screening of NM uptake, HCA, High throughput flow cytometry, Impedance‐based monitoring, Multiplex analysis of secreted products, and genotoxicity methods—namely High throughput comet assay, High throughput in vitro micronucleus assay, and γH2AX assay. There are several technical challenges with HTS/HCA for NM testing, as toxicity screening needs to be coupled with characterization of NMs in exposure medium prior to the test; possible interference of NMs with HTS/HCA techniques is another concern. Advantages and challenges of HTS/HCA approaches in NM safety are discussed. WIREs Nanomed Nanobiotechnol 2017, 9:e1413. doi: 10.1002/wnan.1413 This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Toxicology and Regulatory Issues in Nanomedicine > Regulatory and Policy Issues in Nanomedicine Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials